A Critical Review of Carbonization Hydrothermal and Pyrolysis for Adsorbent Production and the Application in Industrial Dye Removal - Nyamiati, Retno Dwi; Putri Restu Dewati; Muhammad Redo Ramadhan; Ika Wahyuning Widiarti; A Hidayat Nurwahid; Nabila Aulia Balqis (Eksergi, 2025)
Biochar is increasingly recognised as a low-cost and efficient adsorbent for removing organic dyes from wastewater. This review outlines recent developments in biochar production, particularly comparing biochars produced via pyrolysis and hydrothermal carbonisation (HTC). While pyrolysis biochar often exhibits a higher surface area, HTC biochar offers improved oxygen-containing functional groups, contributing to enhanced dye affinity. Studies indicate that biochar can achieve adsorption capacities ranging from 2 to 1353.09 mg/g for dyes such as methylene blue and crystal violet, comparable to or exceeding that of pyrolysis-derived biochars. The review also highlights characterisation techniques such as XRD, FTIR spectroscopy, and SEM to evaluate surface functionality, porosity, and morphology, which directly influence adsorption performance. Practical implications include the suitability of HTC biochar for low-energy, decentralised wastewater treatment systems, particularly in textile and dyeing industries. By connecting production parameters with biochar properties, this review provides insights into optimizing biochar as an adsorbent, particularly for the treatment of dye-contaminated wastewater.